Sex Differences in Pulmonary Hypertension - Rodriguez-Arias, Juan José; García-Álvarez, Ana (Frontiers in Aging, 2021)
Pulmonary hypertension (PH) includes multiple diseases that share as common characteristic an elevated pulmonary artery pressure and right ventricular involvement. Sex differences are observed in practically all causes of PH. The most studied type is pulmonary arterial hypertension (PAH) which presents a gender bias regarding its prevalence, prognosis, and response to treatment. Although this disease is more frequent in women, once affected they present a better prognosis compared to men. Even if estrogens seem to be the key to understand these differences, animal models have shown contradictory results leading to the birth of the estrogen paradox. In this review we will summarize the evidence regarding sex differences in experimental animal models and, very specially, in patients suffering from PAH or PH from other etiologies.